Proposal of a teleoperated hybrid robot for the dismantling of explosive devices (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2021)
One of the greatest threat factors for the civilian and military population in the national territory and in much of the world are improvised explosive devices (IED), landmines, among other types of explosives. For this reason, the research proposal in this document focuses on the proposal and modeling of a teleoperated hybrid robot for the deactivation or controlled detonation of certain explosive devices, taking into account that close interaction with this type of device is dangerous and in some lethal cases and should be avoided. The robot proposed in the document is made up of a mobile platform which has an arm with three (3) degrees of freedom attached and has a caterpillar type traction, the final actuator of the arm will be a disruptor gun with which deactivation is intended. and / or the destruction of electrical components of explosive devices. The main structure will have a camera which will be in charge of sending images of the environment to the control unit in real time, which allows the operator to carry out missions in different environments and thus guarantee the safety of the operator and that of the team.
Keywords: Disruptor cannon; The hybrid robot